Modelling [C i] emission from turbulent molecular clouds - Glover, Simon; Clark, Paul C.; Micic, Milica; Molina Hernandez, Faviola Zuhé (Monthly notices of the Royal Astronomical Society, 2015)
Abstract: We use detailed numerical simulations of a turbulent molecular cloud to study the usefulness of the [C I] 609 and 370 μm fine structure emission lines as tracers of cloud structure. Emission from these lines is observed throughout molecular clouds, and yet they have attracted relatively little theoretical attention. We show that the widespread [C I] emission results from the fact that the clouds are turbulent. Turbulence creates large density inhomogeneities, allowing radiation to penetrate deeply into the clouds. As a result, [C I] emitting gas is found throughout the cloud. We examine how well [C I] emission traces the cloud structure, and show that the 609 μm line traces column density accurately over a wide range of values. For visual extinctions greater than a few, [C I] and 13CO both perform well, but [C I] performs better at AV ≤ 3. We have also studied the distribution of [C I] excitation temperatures. We show that these are typically smaller than the kinetic temperature, indicating that the carbon is subthermally excited. We discuss how best to estimate the excitation temperature and the carbon column density, and show that the latter tends to be systematically underestimated. Consequently, estimates of the atomic carbon content of real giant molecular clouds could be wrong by up to a factor of 2.